In Vivo Immuno‐Spin Trapping: Imaging the Footprints of Oxidative Stress. Issue 1 (1st October 2015) - Khoo, Nicholas K.H.; Cantu‐Medellin, Nadiezhda; St. Croix, Claudette; Kelley, Eric E.
Abstract: A plethora of disease processes are associated with elevated reactive species formation and allied reactions with biomolecules that alter cell signaling, induce overt damage, and promote dysfunction of tissues. Unfortunately, effective detection of reactive species in tissues is wrought with issues that significantly limit capacity for validating species identity, establishing accurate concentrations, and identifying anatomic sites of production. These shortcomings reveal the pressing need for new approaches to more precisely assess reactive species generation in vivo. Herein, we describe an in vivo immuno‐spin trapping method for indirectly assessing oxidant levels by detecting free radicals resulting from reaction of oxidants with biomolecules to form stable, immunologically detectable nitrone‐biomolecular adducts. This process couples the reactivity and sensitivity of an electron paramagnetic resonance spin trap with the resolution of confocal imaging to visualize the extent of cell and tissue oxidation and anatomic sites of production by detecting resultant free radical formation. © 2015 by John Wiley & Sons, Inc.